Transformasional Kepala Sekolah Dalam Program Parenting Wali Untuk Meningkatkan Mutu Siswa - Kitri (STIT Muhammadiyah Bangil Pasuruan, 2025)
This study aims to analyze the role of the principal's transformational leadership in implementing a parenting program to improve student quality at MTS Permata, Muneng Village. This study used a qualitative method with data collection techniques through observation, interviews, and document studies. Data were analyzed based on the theory of Miles and Huberman, which includes three steps: data condensation, data presentation, and conclusion drawing. The main theories used are the transformational leadership theory by Bass and Avolio (1994) and the parental involvement theory by Epstein (2011). The research subjects involved 1 principal as the main informant and 15 parents as participants. The results showed that the principal's transformational leadership plays a strategic role in building collaborative relationships with parents through a parenting program. This program includes regular communication sessions, parenting skills training, and student development evaluations. The implications of this program create increased parental participation in the educational process, as well as improving student quality in academic and non-academic aspects. This study recommends strengthening collaborative-based parenting programs to support the sustainability of educational quality.